PENGARUH LINGKUNGAN KERJA DAN BUDAYA KERJA TERHADAP KEPUASAN KERJA DAN KINERJA PEGAWAI PADA INSPEKTORAT KABUPATEN BADUNG: The Effect of Work Environment and Work Culture on Job Satisfaction and Employee Performance at the Badung Regency Inspectorate - Juliawati, Ni Komang; Dewi, Luh Komang Candra; Santika, I Putu; Antari, Ni Luh Sili (Ganec Swara, 2025)
This study aims to determine the influence of work environment, work culture, and job satisfaction on employee performance at the Inspectorate of Badung Regency. This research uses a quantitative approach, aiming to test or measure the influence between independent variables and the dependent variable. The sample in this study consisted of 87 employees, using the total population sampling method. Data collection was carried out using a questionnaire with a Likert scale. The results of this study show that the work environment, work culture, and job satisfaction have a positive and significant effect on employee performance at the Inspectorate of Badung Regency. The suggestions from this research include maintaining comfort in the workplace, improving employee competencies and skills, and ensuring work effectiveness is upheld